CONCEPTUAL MAPPING ON THE PARABLE OF THE GOSPEL OF LUKE: A COGNITIVE APPROACH - Raymundus P. Lokangleu; Ni Nyoman Tri Sukarsih; Komang Tri Sutrisna Agustia (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTThis thesis presents a cognitive approach in order to identify the categories of conceptualmetaphor and to know the conceptual mapping of those conceptual metaphors found onthe parable of the Gospel of Luke.The qualitative research method was used to analyzethedata in the parable of Luke and supported by purposive sampling technique. Theconceptual metaphor theory by Lakoff and Johnson (1980, 1993, 2003) was used todistinguished the categories of metaphor which are orientational, ontological, andstructural which then mapped into different kinds of conceptual metaphormappings.Firstly, the data were collected, selected, and classified into three metaphoricalcategories which are orientational, ontological, and structural metaphor. Then, the datawere analyzed to find the correspondence of source domain and concrete domain andfrom there the data were mapped through conceptual mapping. The findings are in theparable of Luke, there are more structural metaphor than the other metaphors which areorientational and ontologicalmetaphor. There are 2 data belong to orientational metaphor,3 data are belong to ontological metaphor, and 7 data are belong to structural metaphor.Keywords: conceptual metaphor, conceptual mapping, correspondencesABSTRAKSkripsi ini menggunakan pendekatan kognitif untuk mengidentifikasi kategori konseptualmetafora dan untuk mengetahui pemetaan konseptual dari metafora yang terdapat dalamperumpamaan injil Lukas. Data dianalisis menggunakan metode penelitian kualitatif dandidukung dengan teknik pengambilan sampel.Teori konseptual metafora dari Lakoff danJohnson (1980, 1993, 2003) digunakan untuk membedakan kategori metafora antara lainmetafora orientasi, ontologis, dan struktural yang kemudian dipetakan ke dalampemetaan konseptual metafora yang berbeda. Pertama-tama data dikumpulkan, dipilih,dan diklasifikasi ke dalam tiga kategori metafora antara lain metafora orientasi,ontologis, dan struktural.Kemudian data dianalisis untuk menemukan korespondensidari ranah sumber dan ranah sasaran dan dari sana, data dipetakan melalui pemetaankonseptual. Hasil yang didapat dalam injil Lukas antara lain terdapat lebih banyakmetafora struktural daripada metafora lain yakni metafora orientasi dan ontologis.Terdapat 2 data yang tergolong metafora orientasi, 3 data tergolong metafora ontologis,dan 7 data tergolong metafora struktural.Kata kunci: metafora konseptual, pemetaan konseptual, korespondensi